The Sociology of food eating and the place of food in society - Poulain, Jean-Pierre (Bloomsbury Academic, 2017)
"A classic text about the social study of food, this is the first English language edition of Jean-Pierre Poulain's seminal work. Tracing the history of food scholarship, The Sociology of Food provides an overview of sociological theory and its relevance to the field of food. Divided into two parts, Poulain begins by exploring the continuities and changes in the modern diet. From the effect of globalization on food production and supply, to evolving cultural responses to food - including cooking and eating practices, the management of consumer anxieties, and concerns over obesity and the medicalization of food - the first part examines how changing food practices have shaped and are shaped by wider social trends. The second part provides an overview of the emergence of food as an academic focus for sociologists and anthropologists. Revealing the obstacles that lay in the way of this new field of study, Poulain shows how the discipline was first established and explains its development over the last forty years. Destined to become a key text for students and scholars, The Sociology of Food makes a major contribution to food studies and sociology. This edition features a brand new chapter and preface, specifically written for the English language edition"-- Provided by publisher.